UJI KONSENTRASI EKSTRAK SERAI WANGI TERHADAP MORTALITAS ULAT GRAYAK JAGUNG - Rusli Rustam; Anggita CinthiaTarigan (DINAMIKA PERTANIAN, 2021)
Fall armyworm (Spodoptera frugiperda J. E. Smith) is a major pest of corn. The usual control is the use of synthetic insecticides, but the continuous or unwise use of synthetic insecticides will harm humans and the environment. Therefore an alternative insecticide, called botanical pesticide that is safe and environmentally friendly such as extract citronella extract (Cymbopogon nardus L.) is needed. The purpose of this study was to obtain an effective extract concentration of Cymbopogon nardus L.to control S. frugiperda. The research was conducted at the Plant Pest Laboratory of the Faculty of Agriculture, Riau University, Pekanbaru. The study was done from August to September 2020. This research used a completely randomized design (CRD), consisting of 6 treatments and 4 replications with the concentration was 2 ml.l-1 water, 4 ml.l-1 water, 6 ml.l-1 water, 8 ml.l-1 water, 10 ml.l-1 water and without extract as a control. The result of the research showed that the concentration of 6 ml.l-1 water was able to control the S. frugiperda and could cause total mortality of 80% with an initial time of death of 6.75 hours after application, 50 lethal times of 40.50 hours.